Bioprospection of rattlesnake venom peptide fractions with anti-adipose and anti-insulin resistance activity in vitro - Meléndez-Martínez, David; Gatica Colima, Ana Bertha; Plenge Tellechea, Luis Fernando; Ortega-Hernández, Erika; Reza-Zaldivar, Edwin Estefan; Carbajal-Sauced, Alejandro; Arnaud-Franco, Gustavo; Antunes-Ricardo, Marilena; Jacobo-Velázquez, Daniel A.; Mayolo-Deloisa, Karla; Lozano, Omar; Rito-Palomares, Marco; et al. (2024)
Animal venoms are natural products that have served as a source of novel molecules that have inspired novel drugs for several diseases, including for metabolic diseases such as type-2 diabetes and obesity. From venoms, toxins such as exendin-4 (Heloderma suspectum) and crotamine (Crotalus durissus terrificus) have demonstrated their potential as treatments for obesity. Moreover, other toxins such as Phospholipases A2 and Disintegrins have shown their potential to modulate insulin secretion in vitro. This suggests an unexplored diversity of venom peptides with a potential anti-obesogenic in Mexican rattlesnake venoms. For that reason, this study explored the in vitro effect of Crotalus venom peptide-rich fractions on models for insulin resistance, adipocyte lipid accumulation, antioxidant activity, and inflammation process through nitric oxide production inhibition. Our results demonstrated that the peptide-rich fractions of C. aquilus, C. ravus, and C. scutulatus scutulatus were capable of reverting insulin resistance, enhancing glucose consumption to normal control; C. culminatus, C. molossus oaxacus, and C. polystictus diminished the lipid accumulation on adipocytes by 20%; C. aquilus, C. ravus, and C. s. salvini had the most significant cellular antioxidant activity, having nearly 80% of ROS inhibition. C. aquilus, C. pyrrhus, and C. s. salvini inhibited nitric oxide production by about 85%. We demonstrated the potential of these peptides from Crotalus venoms to develop novel drugs to treat type-2 diabetes and obesity. Moreover, we described for the first time that Crotalus venom peptide fractions have antioxidant and inflammatory properties in vitro models.